2021
DOI: 10.1002/aqc.3595
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution patterns of fish egg and larval assemblages in the lower reach of the Yangtze River: Potential implications for conservation and management

Abstract: 1. River fish diversity is threatened by anthropogenic environmental alteration to landscapes. The early life-history stages of fish play an important role in maintaining diversity and population recruitment and can be heavily influenced by landscape patterns. Information on temporal and spatial distribution patterns of fish eggs and larvae is also important for biodiversity conservation and management of fish resources.2. The Yangtze River possesses a high diversity of fishes, including many commercially impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 60 publications
(69 reference statements)
0
6
0
Order By: Relevance
“…Limnological attributes of floodplain lakes are thought to provide better physical characteristics than in the main channel for the reproduction of some freshwater fish, such as higher water temperatures, lower turbidity, and cleaner and shallower habitats (Lorig et al, 2013). In our previous research, daily water temperature collecting at HK, AQ and JJ locations showed an obvious longitudinal pattern increasing in the upstream direction especially in early spawning months (Ren et al, 2021). For example, the mean value of water temperature was 22.3°C at HK, which was significantly higher than at AQ (21.8°C) and in turn higher than at JJ (21.5°C) in the early spawning season (from Mid‐April to June) (Ren et al, 2021; Appendix S1).…”
Section: Discussionmentioning
confidence: 78%
See 4 more Smart Citations
“…Limnological attributes of floodplain lakes are thought to provide better physical characteristics than in the main channel for the reproduction of some freshwater fish, such as higher water temperatures, lower turbidity, and cleaner and shallower habitats (Lorig et al, 2013). In our previous research, daily water temperature collecting at HK, AQ and JJ locations showed an obvious longitudinal pattern increasing in the upstream direction especially in early spawning months (Ren et al, 2021). For example, the mean value of water temperature was 22.3°C at HK, which was significantly higher than at AQ (21.8°C) and in turn higher than at JJ (21.5°C) in the early spawning season (from Mid‐April to June) (Ren et al, 2021; Appendix S1).…”
Section: Discussionmentioning
confidence: 78%
“…In our previous research, daily water temperature collecting at HK, AQ and JJ locations showed an obvious longitudinal pattern increasing in the upstream direction especially in early spawning months (Ren et al, 2021). For example, the mean value of water temperature was 22.3°C at HK, which was significantly higher than at AQ (21.8°C) and in turn higher than at JJ (21.5°C) in the early spawning season (from Mid‐April to June) (Ren et al, 2021; Appendix S1). In the present research, the total magnitude of larval abundance increased longitudinally in the upstream direction, and the spawning time and duration of reproduction for all eight dominant species (six river–lake migratory and two lake–sedentary species) also showed an earlier spawning period or increased spawning duration in the same direction (Table 2; Figure 5).…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations